2013
DOI: 10.1038/nm.3356
|View full text |Cite
|
Sign up to set email alerts
|

Chloride extrusion enhancers as novel therapeutics for neurological diseases

Abstract: The K+-Cl− cotransporter KCC2 is responsible for maintaining low Cl− concentration in neurons of the central nervous system (CNS), essential for postsynaptic inhibition through GABAA and glycine receptors. While no CNS disorders have been associated with KCC2 mutations, loss of activity of this transporter has emerged as a key mechanism underlying several neurological and psychiatric disorders including epilepsy, motor spasticity, stress, anxiety, schizophrenia, morphine-induced hyperalgesia and chronic pain1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
333
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(352 citation statements)
references
References 45 publications
10
333
0
Order By: Relevance
“…Suppression of KCC2 during enhanced excitation is thought to alter the balance of excitation and inhibition that in turn may lead to anomalous activity such as seizures (Huberfeld et al, 2007;Rivera et al, 2002Rivera et al, , 2004. Surprisingly, we have found that enhancing KCC2 activity with CLP257 (Gagnon et al, 2013) increased the duration of ictal events without affecting their interval of occurrence. These results suggest that downregulation of KCC2 might not be the cause of seizures in epilepsy but rather an adaptive mechanism to prevent the increase in extracellular [K + ] due to the excessive activation of GABA A receptors and KCC2 activity.…”
Section: Enhancing Kcc2 Activity Modulates Epileptiform Activitymentioning
confidence: 55%
See 1 more Smart Citation
“…Suppression of KCC2 during enhanced excitation is thought to alter the balance of excitation and inhibition that in turn may lead to anomalous activity such as seizures (Huberfeld et al, 2007;Rivera et al, 2002Rivera et al, , 2004. Surprisingly, we have found that enhancing KCC2 activity with CLP257 (Gagnon et al, 2013) increased the duration of ictal events without affecting their interval of occurrence. These results suggest that downregulation of KCC2 might not be the cause of seizures in epilepsy but rather an adaptive mechanism to prevent the increase in extracellular [K + ] due to the excessive activation of GABA A receptors and KCC2 activity.…”
Section: Enhancing Kcc2 Activity Modulates Epileptiform Activitymentioning
confidence: 55%
“…In addition, expression and function of KCC2 are tightly regulated by neuronal activity in a way that enhanced excitation results in suppression of KCC2 activity (Huberfeld et al, 2007;Rivera et al, 2002Rivera et al, , 2004. Indeed, restoring KCC2 activity by application of CLP257 increased the duration of isolated GABAergic events (Gagnon et al, 2013).…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andmentioning
confidence: 99%
“…This might be important for finetuning the operational mode of KCC2 and to integrate different signaling pathways. These findings also imply that drugs aimed to modify KCC2 phosphorylation for therapeutic benefit (36,73) have to be investigated under different conditions as their effect might depend on the conformational state of KCC2 and therefore be highly context-specific. Functional cross-talk between different regions has also been suggested for NKCC1, where phosphorylation of the N terminus causes movement of the C terminus, which in turn entails altered interactions between different transmembrane domains (74).…”
Section: Discussionmentioning
confidence: 99%
“…2013). Although the precise mechanism of the drug action on KCC2 is currently unknown, CLP257 was able to act as a chloride extrusion enhancer in a neuropathic pain model, and restore Cl − transport in adult spinal cord slices with impaired KCC2 function.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
“…While the compound itself exhibited modest binding to adenosine receptors and other classes of GPCRs (Gagnon et al . 2013), future studies must systematically examine whether G q ‐GPCR agonists could also work as novel Cl − extrusion enhancers under physiological and/or pathological states.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%